Formulation of Synthesized Zinc Oxide Nanopowder into Hybrid Beads for Dye Separation. (9th April 2014) - Shokry Hassan, H.; Elkady, M. F.; El-Shazly, A. H.; Bamufleh, Hisham S.
Abstract : The sol-gel prepared zinc oxide nanopowder was immobilized onto alginate-polyvinyl alcohol polymer blend to fabricate novel biocomposite beads. Various physicochemical characterization techniques have been utilized to identify the crystalline, morphological, and chemical structures of both the fabricated zinc oxide hybrid beads and their corresponding zinc oxide nanopowder. The thermal stability investigations demonstrate that ZnO nanopowder stability dramatically decreased with its immobilization into the polymeric alginate and PVA matrix. The formulated beads had very strong mechanical strength and they are difficult to be broken up to 1500 rpm. Moreover, these hybrid beads are chemically stable at the acidic media (pH < 7) especially within the pH range of 2–7. Finally, the applicability of the formulated ZnO hybrid beads for C.I. basic blue 41 (BB41) decolorization from aqueous solution was examined.